2023
DOI: 10.1007/s11044-023-09884-x
|View full text |Cite
|
Sign up to set email alerts
|

Multibody dynamics and control using machine learning

Abstract: Artificial intelligence and mechanical engineering are two mature fields of science that intersect more and more often. Computer-aided mechanical analysis tools, often multibody system software, are very versatile and have revolutionalized many industries. However, as shown by the literature presented in this review, combining the advantages of multibody system dynamics and machine learning creates new and exciting possibilities. For example, the multibody method can assist machine learning by providing synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 133 publications
0
6
0
1
Order By: Relevance
“…Ši tinklo struktūra buvo pasiūlyta Hochreiter ir Schmidhuber (1997) siekiant išspręsti nykstančių gradientų problemą, kuri pasireiškia įprastuosiuose rekurentiniuose neuronų tinkluose. ITAT tinklo neuronai pakeičiami atminties celėmis, kur kiekviena celė turi keturis pagrindinius komponentus: įvesties vartus, užmaršties vartus, kandidato nustatymą ir išvesties vartus (Zhang et al, 2019;Hashemi et al, 2023). Šie elementai nustato, kaip informacija patenka į celę, iš jos ir viduje.…”
Section: Dirbtinių Neuronų Tinklai Su Dinaminėmis Sinapsėmisunclassified
“…Ši tinklo struktūra buvo pasiūlyta Hochreiter ir Schmidhuber (1997) siekiant išspręsti nykstančių gradientų problemą, kuri pasireiškia įprastuosiuose rekurentiniuose neuronų tinkluose. ITAT tinklo neuronai pakeičiami atminties celėmis, kur kiekviena celė turi keturis pagrindinius komponentus: įvesties vartus, užmaršties vartus, kandidato nustatymą ir išvesties vartus (Zhang et al, 2019;Hashemi et al, 2023). Šie elementai nustato, kaip informacija patenka į celę, iš jos ir viduje.…”
Section: Dirbtinių Neuronų Tinklai Su Dinaminėmis Sinapsėmisunclassified
“…To corroborate the ever growing link between multibody dynamics and artificial intelligence, several very recent studies show that combining the advantages of multibody system dynamics and machine learning is creating new possibilities and opportunities [23]. For instance, a method to replace the multibody-based equations of motion of arbitrary systems was proposed in [24] by using a deep neural network-based modeling technique, with the goal to improve computational efficiency.…”
Section: Paper Contributionsmentioning
confidence: 99%
“…Adaptive control relies on tuning control parameters, which can be time-consuming and challenging to perform in real time. To address those challenges, research on using RL is conducted [4].…”
Section: Reinforcement Learning In Multibody System Dynamicsmentioning
confidence: 99%
“…A paper by Hashemi et al [4] provides an overview of how Machine Learning might be applicable to Multibody System Dynamics. Specifically talking about RL, the authors show that its use has recently been suggested for a wide variety of tasks: starting from improving feedback control systems and robotic applications by ending with assistance in simulating human movements.…”
Section: Introductionmentioning
confidence: 99%